Formic Acid Pulping and TCF Bleaching of Cassava Stalks (Dhaka University Journal of Applied Science and Engineering, 2022)
The formic acid (FA) pulping process is well-known for its advantage to overcome the problems caused by the presence of high silica and fines content of agriculture residues during pulping. In this context a new and unconventional raw material, cassava stalk was pulped using formic acid followed by treatment withperoxyformic acid (PFA) treatment was applied to the formic acid treated pulps at 800C for two hours.It was found that the FA/PFA process lowered pulp yield of cassava stalks when FA concentration was increased. The PFA pulping decreased the kappa number of the pulps. After the FA/PFA treatment of cassava stalks, the pulp yield reached 37- 42% with kappa number of 21-34 at different formic acid concentrations. FA/PFA pulp from cassava stalks did not show promising result in total chlorine free bleaching and final brightness reached only up to 54%.DUJASE Vol. 6 (2) 1-6, 2021 (July)